The effectiveness of insulin glargine 300 U/mL among type 2 diabetes patients: Analysis of a real‐world data in Israel. Issue 3 (24th March 2020) - Melzer Cohen, Cheli; Banon, Tamar; Shalev, Varda; Chodick, Gabriel
Abstract: Aims: Randomized controlled trials have shown that insulin glargine 300 U/mL (Gla‐300) has a more stable and prolonged glucose lowering effect among patients with type 2 diabetes (T2DM) compared to insulin glargine 100 U/mL (Gla‐100), resulting in a reduced risk of hypoglycaemia while maintaining a similar efficacy of lowering HbA1c . We aimed to investigate if the effectiveness of Gla‐300 is reproducible in real‐world settings. Material and methods: In this retrospective cohort study, data from a large state‐mandated health organization were used to identify adult T2DM patients who were previously on insulin and initiated Gla‐300 therapy between 6/ 2016 and 12/2017. Changes in HbA1c levels, body weight and insulin dose were calculated from baseline period and over a follow‐up period of 180 days. Documented hypoglycaemia events were also explored. Results: A total of 1797 patients were included in this study with a mean age of 64.2 (SD = ±11.0y), baseline HbA1c was 8.7 ± 1.6% and 42.5% were females. Among all patients with HbA1c measurement during follow‐up (n = 1508), HbA1c was significantly reduced by −0.6% (95% CI −0.6, −0.5; P  < .001) from baseline, with a significant reduction in body weight (−0.4 kg; P  = <.001). Additionally, a significant ( P  = .04) reduction of 40.5% in patients with hypoglycaemia events was recorded during follow‐up period, from 2.1% (n = 37) at the baseline period to 1.2% (n = 22). Conclusions: This real‐world study supports evidence from RCTs regarding the effectiveness of Gla‐300 among T2DM patients by improving glycaemic control. Abstract : In this real‐world study, the effectiveness and safety among 1797 type 2 diabetes patients were investigated. The article provides evidence that insulin glargine 300 is effective in reducing blood glucose levels without increasing body weight or hypoglycaemic events.